CircRNA75 and CircRNA72 Function as the Sponge of MicroRNA-200 to Suppress Coelomocyte Apoptosis Via Targeting Tollip in Apostichopus japonicus - Liu, Jiqing; Zhao, Xuelin; Duan, Xuemei; Zhang, Weiwei; Li, Chenghua (Frontiers in Immunology, 2021)
Circular RNAs (circRNAs) act as essential regulators in many biological processes, especially in mammalian immune response. Nonetheless, the functions and mechanisms of circRNAs in invertebrate immune system are largely unclariﬁed. In our previous work, 261 differentially expressed circRNAs potentially related to the development of Apostichopus japonicus skin ulceration syndrome (SUS), which is a major problem restricting sea cucumber breeding industry, were identified by genome-wide screening. In this study, via miRanda analysis, both circRNA75 and circrRNA72 were shown to share the miR-200 bind site, a key microRNA in the SUS. The two circRNAs were verified to be increased significantly in LPS-exposed primary coelomocytes, similar to the results of circRNA-seq in sea cucumber under Vibrio splendidus-challenged conditions. Dual-luciferase assay indicated that both circRNA75 and circRNA72 could bind miR-200 in vivo, in which circRNA75 had four binding sites of miR-200 and only one for circRNA72. Furthermore, we found that miR-200 could bind 3’-UTR of Toll interacting protein (Tollip) to negatively mediate the expression of Tollip. Silencing Tollip increased primary coelomocyte apoptosis. Consistently, inference of circRNA75 and circRNA72 could also down-regulate Tollip expression, thereby increasing the apoptosis of primary coelomocytes, which could be blocked by miR-200 inhibitor treatment. Moreover, the rate of si-circRNA75 down-regulated Tollip expression was higher than that of si-circRNA72 under equivalent amount conditions. The circRNA75 and circRNA72 suppressed coelomocyte apoptosis by sponging miR-200 to promote Tollip expression. The ability of circRNA to adsorb miRNA might be positively related to the number of binding sites for miRNA.